2001
DOI: 10.1023/a:1010531802372
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Bovine tuberculosis in dairy cattle in Asmara, Eritrea, was studied using a cross-sectional study to describe its prevalence and to identify factors associated with it. A total of 72 randomly selected herds were included in the study. The comparative intradermal tuberculin test was used for the diagnosis. Of 1813 individual animals tested, 14.5% were reactors. Thirty herds (41.7%) had at least one reactor but, by defining a reactor herd as any herd with two or more reactors, only 19 (26.4%) herds were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 4 publications
2
13
2
Order By: Relevance
“…In 1998, a cross-sectional study carried out on 1 813 animals (494 intensive dairy farms) of Eritrea suggested that imported breeds, used to improve the dairy industry in tropical areas, may be less resistant to bTB compared to indigenous breeds, e.g. zebu [88]. Elias et al.…”
Section: Risk Factors At the Animal Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, a cross-sectional study carried out on 1 813 animals (494 intensive dairy farms) of Eritrea suggested that imported breeds, used to improve the dairy industry in tropical areas, may be less resistant to bTB compared to indigenous breeds, e.g. zebu [88]. Elias et al.…”
Section: Risk Factors At the Animal Levelmentioning
confidence: 99%
“…A cross-sectional study on 1 813 animals from 494 herds carried out in Eritrea in 2001 suggested that farm size (surface), was a risk factor for bTB but no information was provided regarding what farm size was considered as being at risk [88]. Farm size, in terms of number of holdings and boundary length, has an impact on bTB risk, as shown in the UK3.…”
Section: Herd-level Risk Factorsmentioning
confidence: 99%
“…Further, the choice of workable control measures and strategies should take into account all key factors unique to each different ecosystem. A number of factors have been observed to be associated with BTB in cattle herds [44]. Oloya and coworkers observed that BTB was associated with different types of drinking water sources [45].…”
Section: Controlmentioning
confidence: 99%
“…The same study also indicated that BTB is linked to specific geographical regions of production although they did not conclusively state the factors responsible for this observation [45]. BTB has also been shown to be associated with communal grazing, animal breed type and husbandry practices [44]. Studies have also shown that herd size has an influence on the prevalence of BTB [12, 30, 31, 46, 47].…”
Section: Controlmentioning
confidence: 99%
“…At individual level, the prevalence of tuberculosis-like lesions has been found to increase with age in cattle and buffalo [14,15]. Different breeds of cattle also experience different risk of BTB [16]. At herd level, factors such as herd size and previous infection status have been identified to correlate with the probability of positive reaction to BTB test [17,18].…”
Section: Introductionmentioning
confidence: 99%